Comparison of Vonoprazan Based H Pylori Eradication Regimen and Omeprazole Based H Pylori Eradication Regimen: A Novel Option - Muhammad Waqas, Umair Riaz Ahmad, Shayan Rashid Khawaja, Asma Mushtaq, Awais Rasheed, Lubna Rafique, (Pakistan Journal of Medical & Health Sciences, 2022)
Background: H Pylori causes a number of conditions related to gastric mucosa. Owing to emerging antibiotic resistance, more treatment options are needed. Vonoprazan (VPZ) is potassium based acid inhibitor and showing promise in H Pylori eradication regimens. Results: The study comprise of total 300. Mean Age of study population was 33.04 + 13.01 years and mean age of VPZ based H. Pylori eradication regimen group was 31.78 + 12.384 and mean age of PPI based H. Pylori eradication regimen group was 34.30 + 13.535 (P-Value 0.428) given in table 1. Gender distribution in study population was 54.3% females and 48% males. Gender Distribution in VPZ based H. Pylori eradication regimen group was 52% females and 48% males and in PPI based H. Pylori eradication regimen group, females were 56.7% and males were 43.3% (P-Value 0.487). Comparison of efficacy of VPZ based H. Pylori eradication regimen and PPI based eradication regimen shows that vonoprazan is more effective in H Pylori eradication as compared to PPI based H.Pylori eradication regimen (P-Value 0.028) Conclusion: Vonoprazan is equally superior as first line therapy H.pylori eradication regimes as PPIs based regime. Eradication rate was higher as compared to PPI. More studies with large sample size in multiple ethnicities are required to establish more effective vonoprazan based regimens against H. Pylori.